Environmental-friendly extraction of chlorophyll from pineapple plantation waste for dye sensitized solar cell (DSSC) fabrication - Noor Fairuz, Md Roskan; Norazwina, Zainol; Ahmad Syahiman, Mohd Shah; Alyaa Afiqah, Zi (2021)
Improper disposal of pineapple waste can cause negative impact to the environment. To reduce the waste, we decide to recycle it. Recently, we discover that the present of chlorophyll in the pineapple plantation waste in the leaves can be used to fabricate the Dye Sensitized Solar Cell (DSSC) which is can be categorised as a renewable energy as well as environmental-friendly. The experimental and analysis was done to obtain the best condition of chlorophyll yield from the waste. The best condition from the mechanical extraction can be achieved by uncut the processed leaves at 3 cycle for extraction cycle by using the sugarcane machine. The highest value of chlorophyll a is 52.57 mg/ml and chlorophyll b is 113.05 mg/ml.